2020
DOI: 10.1002/dev.21962
|View full text |Cite
|
Sign up to set email alerts
|

Presence of mother prompts dissociation of sickness behavior, fever, and hypothalamic gene expression in lipopolysaccharide‐injected guinea pig pups

Abstract: During infection, sickness behaviors, such as a hunched stance with piloerection, can facilitate host resistance by supporting the generation and maintenance of fever. Fever, in turn, is mediated by hypothalamic neuroimmune signaling. Sickness behaviors, however, can also be influenced by social stimuli. In this study, guinea pig pups were injected with lipopolysaccharide to simulate a bacterial infection and then exposed to a novel, threatening environment while either with their mother or alone. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…They found that sickness can either increase or decrease social behaviors [reviewed by ( 17 )]. A recent paper reported that sickness behaviors and fever can be disassociated in LPS-injected guinea pig pups, depending upon whether LPS is injected with their mother nearby ( 18 ). Presence of the mother enhanced LPS-induced fever in the pups even though sickness behaviors were nearly absent.…”
Section: Sickness Behaviorsmentioning
confidence: 99%
“…They found that sickness can either increase or decrease social behaviors [reviewed by ( 17 )]. A recent paper reported that sickness behaviors and fever can be disassociated in LPS-injected guinea pig pups, depending upon whether LPS is injected with their mother nearby ( 18 ). Presence of the mother enhanced LPS-induced fever in the pups even though sickness behaviors were nearly absent.…”
Section: Sickness Behaviorsmentioning
confidence: 99%
“…Furthermore, the peripheral immunomodulatory effects of stress differ between stressors that are socially neutral (such as restraint stress and foot‐shock stress, which tend to be adaptively immuno‐enhancing for the individual) and stressors that have powerful social meaning and adaptive consequences for social life. [ 100 ] For instance, CSDS (which tends to be immunosuppressive) is characterized by a specific pattern of peripheral T cell responses associated with social defeat. [ 101 ]…”
Section: Microglia Transduce Environmental Influences Into Developmenmentioning
confidence: 99%
“…A recent review ( Kelley and Kent, 2020 ) emphasizes the reciprocal communication between the immune system and the brain, and provides examples showing that sickness behavior and fever can be dissociated by social stimuli. Guinea pig pups that were given LPS to induce fever, if the mother were present, had the enhanced fever but not the sickness behavior ( Hennessy et al, 2020 ). A study of febrile and non-febrile children documented the independence of sickness behavior and fever ( Corrard et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%